PENGARUH LEVERAGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Nindiana, Nindiana (COMPETITIVE, 2021)
The purpose of this study is to analyze and ascertain the influence of leverage, profitability, and corporate size on tax avoidance both partially and simultaneously on food and beverage sub-sector companies in the period 2017-2019 on the IDX. The data in this study was tested using SPSS version 22 software with multiple linear regressions. The results obtained in this study were that partial leverage and profitability had no effect on tax avoidance, partially the size of the company negatively affected tax avoidance, and simultaneously the leverage, profitability, and size of the company had an effect on tax avoidance and all three variables could affect as much as 18.5%.